2003
DOI: 10.1590/s0365-05962003000600006
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis em João Pessoa: visão socioeconômica

Abstract: FUNDAMENTOS: A distribuição das espécies de dermatófitos varia ao longo do tempo e de acordo com a região, refletindo as condições socioeconômicas da população OBJETIVOS: Estudar a Tinea Capitis quanto ao agente etiológico, ao sexo, à idade e ao grupo étnico dos doentes em João Pessoa, PB, Brasil e salientar a importância socioeconômica desses dados, comparando-os aos de regiões mais ricas do país. MÉTODOS: Foram avaliados o perfil e os exames micológicos direto e cultura de 82 pacientes com suspeita clínica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Corroborating these studies, Wael et al (2015), in their study, observed that 7.2% of the analyzed samples of human beings tested positive for T. verrucosum, where they were people who had cattle, sheep and goats. Aquino et al (2003), in their study carried out in João Pessoa, observed that T. verrucosum was found in the fourth position among the positive samples for dermatophytosis in human beings, representing 10% of the observed cases. Santos et al (2021), observed in their study with dogs and cats, percentages representing 14.2% of positive samples for fungi, also demonstrating that a relevant percentage of their owners also reported having similar skin lesions, fact that can be explained by the close interaction between the owners and their animals, which facilitates the zoonotic transmission of these agents, highlighting the fact that many of these owners were unaware of the term zoonosis, revealing the need for investment in health education, addressing issues related to One Health, aiming at the prevention of occurrence of these diseases in animals and consequently in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Corroborating these studies, Wael et al (2015), in their study, observed that 7.2% of the analyzed samples of human beings tested positive for T. verrucosum, where they were people who had cattle, sheep and goats. Aquino et al (2003), in their study carried out in João Pessoa, observed that T. verrucosum was found in the fourth position among the positive samples for dermatophytosis in human beings, representing 10% of the observed cases. Santos et al (2021), observed in their study with dogs and cats, percentages representing 14.2% of positive samples for fungi, also demonstrating that a relevant percentage of their owners also reported having similar skin lesions, fact that can be explained by the close interaction between the owners and their animals, which facilitates the zoonotic transmission of these agents, highlighting the fact that many of these owners were unaware of the term zoonosis, revealing the need for investment in health education, addressing issues related to One Health, aiming at the prevention of occurrence of these diseases in animals and consequently in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Nos EUA, em 2002, foi diagnosticado um caso em um paciente de 22 anos, ocasionado por uma espécie do gênero Trichophyton 64 . No Brasil, em um estudo na Paraíba, verificou-se a incidência em 1% da população 65 .…”
Section: Formas Clínicasunclassified
“…12 In Brazil, various studies, shown in chart 1, have registered a higher frequency of T. tonsurans in northern and northeastern states and M. canis in southern and southeastern states. [13][14][15][16][17][18][19][20][21] T. schoenleinii infection, which causes tinea favosa, has been shown to be quite rare in the cited regions and countries. 22 This had the goal of adding up epidemiological data on the matter, based on data obtained at the Dermatology Department at Botucatu Medical School-Unesp (Dermatology-FMB), which sees both urban and rural population coming from the interior of the State of São Paulo.…”
Section: Introductionmentioning
confidence: 99%